The Poet and the Evangelist in Nonnus’ Paraphrase of the Gospel according to John - Hadjittofi, Fotini (2020)
The published article can be viewed here: https://www.cambridge.org/core/journals/cambridge-classical-journal/article/poet-and-the-evangelist-in-nonnus-paraphrase-of-the-gospel-according-to-john/CC5AC20755E63E6D55571A36D4AAA879/share/6072b171966615b29e7385e890edbf811e1f7b2d